2019
DOI: 10.1007/s10815-019-01482-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of daily vaginal progesterone gel plus weekly intramuscular progesterone with daily intramuscular progesterone for luteal phase support in single, autologous euploid frozen-thawed embryo transfers

Abstract: Purpose To compare outcomes between daily intramuscular progesterone (IMP) and daily vaginal progesterone (VP) gel plus weekly intramuscular hydroxyprogesterone caproate (IMHPC) for luteal phase support (LPS) in single, autologous euploid frozen-thawed blastocyst transfers (FBTs) following artificial endometrial preparation (EP). Methods The retrospective cohort study included 767 single, autologous FBTs from 731 patients between January 2015 and March 2018. LPS was performed either with IMP (100 mg/day) or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This may additionally reflect the phenomenon of first uterine pass, whereby a targeted delivery of vaginal progesterone to the uterus enhances the local endocrine milieu and hence facilitates implantation and pregnancy success (60). Overall, however, studies comparing different routes and regimens of LPS in FET have failed to categorically identify a formulation with superior results (42,47,(61)(62)(63)(64)(65).…”
Section: Summary Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…This may additionally reflect the phenomenon of first uterine pass, whereby a targeted delivery of vaginal progesterone to the uterus enhances the local endocrine milieu and hence facilitates implantation and pregnancy success (60). Overall, however, studies comparing different routes and regimens of LPS in FET have failed to categorically identify a formulation with superior results (42,47,(61)(62)(63)(64)(65).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…There were originally concerns with reduced bioavailability of natural progesterone due to its large molecular size, but in its micronized form progesterone has since been shown to be easily absorbed by the vaginal and intestinal mucosa (66,67). Furthermore, gel-based formulations containing micronized progesterone exhibit a sustained-release mechanism which leads to steady levels of absorption over time and prevents excessive variation in serum progesterone levels (63,64). The vaginal formulation is most commonly used in ART treatment across the world, and the preferred route of administration for up to one in four ART practitioners (68).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…However, we did not detect any difference between agonist and antagonist groups with respect to BPR and LBR. Two other studies analyzed VP in comparison to IMP for luteal phase support and found that VP resulted in better clinical pregnancy outcomes that could be due to progesterone's local effect inducing secretory transformation of the endometrial stroma (Ho et al ., 2008; Satir et al ., 2013 ; Asoglu et al ., 2019 ). This study is limited due to its retrospective design.…”
Section: Discussionmentioning
confidence: 99%
“…By far, the pharmaceutical industry has developed several different dosage forms of progesterone available for intramuscular injection, oral and vaginal administration 7–10 . When encapsulated in the soft capsule, micronized progesterone can be absorbed through the gastrointestinal tract or vaginal mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…6 By far, the pharmaceutical industry has developed several different dosage forms of progesterone available for intramuscular injection, oral and vaginal administration. [7][8][9][10] When encapsulated in the soft capsule, micronized progesterone can be absorbed through the gastrointestinal tract or vaginal mucosa. Progesterone exhibits linear and dose-dependent pharmacokinetics under multiple doses ranging from 100 to 300 mg/day in postmenopausal women.…”
mentioning
confidence: 99%